As elites de Santo Antônio - poder, representações e sociablidade - o caso da Irmandade do Santíssimo Sacramento (1791-1822) - SILVA, Welber Carlos Andrade da (2012)
This work scrutinizes the formation of Recife's elites during the XVIII century and its relation with institutions such as the City Council and the Brotherhood of the Santíssimo Sacramento de Santo Antonio of Recife. The work is based on a social approach to understand the social types that participated in these institutions, privileging the role of the elites, especially in the Brotherhood. In this perspective, we used a vast literature that covers the lives of some of the most important men of Recife between the years of 1791 and 1822. Thus, we work on the Recife scene and the operation of the Brotherhood as a space of sociability, representation and power. The literature used is comprised of attendance sheets, recipe books, commitment and Brotherhood of the Santíssimo Sacramento logbooks, and miscelaneous documents from the Ultramarine History Archive, made available through the “Projeto Resgate". Based on the utilized literature, we assemble a prosopographical chart that allows us to analyze the social origins of some members of the brotherhood and the roles that they performed inside and outside of the brotherly environment.